2023
DOI: 10.1108/gkmc-06-2023-0218
|View full text |Cite
|
Sign up to set email alerts
|

Instilling employees with meaning to communicate: servant leadership affecting employee voice behavior through meaning

Muhammad Mumtaz Khan,
Muhammad Shujaat Mubarik,
Syed Saad Ahmed
et al.

Abstract: Purpose This study aims to analyze the connection between servant leadership and the promotive and prohibitive voice behavior of employees. In addition, this study explained how servant leadership affects promotive and prohibitive voice behavior through meaning. Design/methodology/approach For this study, data were collected from employee–manager dyads employed in the service sector. Each of the waves was initiated two months after the first wave. Finally, 286 useful responses were obtained. The collected da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Yet, more and more studies have shown that nurses exhibit low voice behavior [3], and Kee et al's study analyzed possible reasons for this, including considering voice behavior as 'risky', being disrespected and ignored, and unexpected outcomes [4]. Furthermore, some low voice behaviors also cause risks of con icts with leaders, the deterioration of interpersonal relationships, and career development obstacles [5]. Therefore, it is important to explore the direct and indirect factors affecting voice behavior in clinical nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, more and more studies have shown that nurses exhibit low voice behavior [3], and Kee et al's study analyzed possible reasons for this, including considering voice behavior as 'risky', being disrespected and ignored, and unexpected outcomes [4]. Furthermore, some low voice behaviors also cause risks of con icts with leaders, the deterioration of interpersonal relationships, and career development obstacles [5]. Therefore, it is important to explore the direct and indirect factors affecting voice behavior in clinical nurses.…”
Section: Introductionmentioning
confidence: 99%